2009
DOI: 10.1158/0008-5472.can-09-0437
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Independence Associated with Tumor Progression

Abstract: Tumor-microenvironment interactions are increasingly recognized to influence tumor progression. To understand the competitive dynamics of tumor cells in diverse microenvironments, we experimentally parameterized a hybrid discretecontinuum mathematical model with phenotypic trait data from a set of related mammary cell lines with normal, transformed, or tumorigenic properties. Surprisingly, in a resource-rich microenvironment, with few limitations on proliferation or migration, transformed (but not tumorigenic)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…Thus, we here simply assume the pay-offs to be a linear gradient when a linear drug gradient is applied. We found that, in regions with higher drug concentrations, ST cells grow more slowly while the most resistant cancer cells survive; this is related to the previous discovery that the most aggressive cancer cells are the least limited by environmental constraints [33].…”
Section: Resultssupporting
confidence: 71%
“…Thus, we here simply assume the pay-offs to be a linear gradient when a linear drug gradient is applied. We found that, in regions with higher drug concentrations, ST cells grow more slowly while the most resistant cancer cells survive; this is related to the previous discovery that the most aggressive cancer cells are the least limited by environmental constraints [33].…”
Section: Resultssupporting
confidence: 71%
“…This may provide a selective advantage to cells that are able to bypass these signals. Computational modeling has predicted that NPCs that are able to proliferate without growth factors could be selected for in this environment, but would have no such competitive advantage in a younger brain with more growth factor availability (Anderson et al ., 2009). Although dysfunction in intracellular signaling as a result of genetic mutation is considered to be the major cause of oncogenic transformation, malignant cells are also able to co-opt the surrounding tissue to create a favorable environment for the growing tumor.…”
Section: Acquisition Of a Highly Proliferative Phenotypementioning
confidence: 99%
“…This framework uses evolutionary game theory (EGT), a mathematical tool that has been traditionally used in evolutionary ecology [4] and more recently in mathematical oncology [5, 6, 7, 8, 9, 10]. This modelling tool has potential to provide insights into the evolutionary dynamics of cancer when a combination therapy is used.…”
Section: 2 Introductionmentioning
confidence: 99%